2008
DOI: 10.1097/sle.0b013e3181805729
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Permanent Sigmoid Stoma Creation Through the Extraperitoneal Route

Abstract: About 50% of patients who have a permanent stoma experience some degree of parastomal hernia formation. To prevent this complication, the extraperitoneal route is considered to be more effective than the transperitoneal route in the case of open colorectal surgery. This technique also has superiority in avoiding postoperative intestinal obstruction. Although laparoscopic surgery for rectal cancer has not been proved to be as safe as open surgery by a randomized-controlled trial, some studies have shown the equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 11 publications
0
20
0
Order By: Relevance
“…This goal was not realized but the authors noted an incidental decrease in the incidence of PSH. A laparoscopic version of this technique has been described [14][15][16]; • the size of the parietal orifice seems be crucial [17]. A prospective study showed that the rate of PSH was directly proportional to the diameter in millimeters of the orifice.…”
Section: Discussionmentioning
confidence: 98%
“…This goal was not realized but the authors noted an incidental decrease in the incidence of PSH. A laparoscopic version of this technique has been described [14][15][16]; • the size of the parietal orifice seems be crucial [17]. A prospective study showed that the rate of PSH was directly proportional to the diameter in millimeters of the orifice.…”
Section: Discussionmentioning
confidence: 98%
“…We applied this technique to laparoscopic APRs as reported previously. 9 Open surgery for APR presents a risk of not only parastomal hernia, but also incisional hernia. On the other hand, because laparoscopic surgery for APR presents a minimal risk of incisional hernia, its application would be beneficial in preventing abdominal herniation.…”
Section: Discussionmentioning
confidence: 99%
“…In group A, the stoma was created through the extraperitoneal route according to our previously reported technique. 9 In brief, a circular opening of the skin was created with a scalpel (diameter, 25 mm) at the site that had been marked preoperatively by the stoma therapist. The fascia was then incised in a crosswise direction approximately 2 finger widths in length.…”
Section: Surgical Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…Hamada et al [22, 23] reported the usefulness of and the proper technique for extraperitoneal colostomy in laparoscopic APR, although the risk factors for hernia formation were not described. Extraperitoneal colostomy may be recommended for patients undergoing laparoscopic APR.…”
Section: Discussionmentioning
confidence: 99%